Steroidal saponins and sapogenins from Agapanthus praecox Willd - Mathew, George Ernest Albert (Department of Chemistry, 2016)
Agapanthin, C₅₁H₈₄O₂₄, a steroidal saponin, isolated from rhizomes of Agapanthus praecox Willd., yielded, on acid hydrolysis, the steroidal sapogenin agspanthagenin and galactose and rhamnose in the molecular ratio of 3:l. The structure assigned to agapanthagenin has been confirmed oh the basis of further synthetic and spectroscopic evidence. The structure of a closely associated steroidal sapogenin, praecoxigenin, C₂₇H₄₀O₄ , has been partially elucidated.